Application of an NVNA-Based System and Load-Independent X-Parameters in Analytical Circuit Design Assisted by an Experimental Search Algorithm - Pelaez-Perez, A. M.; Woodington, S.; Fernandez-Barciela, M.; Tasker, P. J.; Alonso, J. I. (IEEE transactions on microwave theory and techniques, 2013)
Recently, X -parameters have been introduced to model active device nonlinear behavior. In addition to providing a measurement-based tool to numerically predict nonlinear device behavior in computer-aided design, they can also provide the designer of nonlinear circuits an analytical design tool. Exploiting this design tool aspect, this work presents an application that combines the nonlinear vector network analyzer PNA-X and a passive tuner to extract a transistor load-independent X -parameter model, focused around targeted circuit impedances for optimal performance. Furthermore, an experimental search algorithm, based on X -parameters analytical computations and developed by Peláez-Pérez , has been used and experimentally validated in this paper, aimed to speed up the characterization and design process, minimizing the number of load-pull measurements necessary to provide an accurate transistor X -parameter model for use in analytical and/or numerical circuit design.